Genomic profiling of cefotaxime-resistant Haemophilus influenzae from Norway and Sweden reveals extensive expansion of virulent multidrug-resistant international clones - Skaare, Dagfinn; Anthonisen, Inger Lill; Zecic, Nermin; Jenkins, Andrew; Caugant, Dominique A.; Ranheim, Trond Egil; Sundsfjord, Arnfinn; Hegstad, Kristin; , Study Group on Exceptional Phenotypes in Haemophilus influenzae; Leegaard, Truls Michael; Dons, Tine Smedsund; Lindemann, Paul Christoffer; et al. (Frontiers in Microbiology, 2025)
Cefotaxime-resistant Haemophilus influenzae (CRHI) are a global concern, but little is known about their molecular epidemiology. The goal of this study was to perform genomic profiling of 191 CRHI from Norway (n = 183) or Sweden (n = 8) (2006–2018) and assess clonal spread using core genome multilocus sequence typing (cgMLST)-based Life Identification Number (LIN) codes based on whole genome sequencing (Ion Torrent). Cefotaxime resistance was confirmed with broth microdilution minimal inhibitory concentration (MIC), interpreted with the European Committee on Antimicrobial Susceptibility Testing (EUCAST) breakpoints. 35.7% of isolates with cefotaxime gradient MIC of 0.25 mg/L were falsely resistant. All but two isolates (blood) were non-invasive, and all but two (serotype f) were non-typeable. Characterization included calling of resistance determinants, ftsI typing (penicillin-binding protein 3, PBP3), and classification of PBP3-mediated beta-lactam resistance (rPBP3), with assignment to rPBP3 stage and group. All isolates had rPBP3-defining substitutions, and 78.5% were stage 3 (L389F positive). Beta-lactam MICs correlated well with rPBP3 genotypes. Significant proportions of stage 3 isolates were cross-resistant to ceftriaxone (86.0%) and meropenem (meningitis breakpoints, 26.0%). The CRHI prevalence in Norway doubled during the study period and approached 1%. A shift from stage 2 to stage 3 rPBP3 in 2011–2012 led to emergence of CRHI with higher beta-lactam MICs and co-resistance to multiple non-beta-lactams, including extensively drug-resistant (XDR) strains. The shift was driven by transformation with two distinct variants of the transpeptidase region and multiclonal expansion. 66.0% of the isolates belonged to 27 clusters. Ten clusters or singletons belonged to international CRHI clones represented in the PubMLST database. The study provides new insight into CRHI evolution, resistance profiles, and clonal dynamics in a period when this phenotype went from exceptional to unusual in Europe. International CRHI clones are described for the first time, including eight high-risk clones associated with invasive disease, calling for enhanced genomic surveillance. LIN coding, supplemented with ftsI typing and rPBP3 staging, is well-suited for definition of CRHI clones. LIN9, defined by ≤ 10 allelic differences, offered the highest resolution level fully supported by maximum likelihood core genome phylogeny and is proposed as a global standard for genomic surveillance of H. influenzae.